Pengaruh kompensasi dan lingkungan kerja fisik terhadap kepuasan kerja karyawan pada PT Media Indo Bersama - Elburdah , Risza Putri; Amalia , Esti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Job satisfaction refers to the level of satisfaction experienced by an individual with their position or work in a company. This study aims to determine the impact of salary and physical work environment on employee job satisfaction. The methodology used is descriptive-quantitative. The sample size for this particular investigation consisted of 63 participants. The sampling methodology used is non-probability sampling, especially saturated sampling. Investigation findings related to the compensation variable (X1) indicate a partial effect of compensation on the level of job satisfaction experienced by employees, as evidenced by the t-test. The physical work environment variable (X2) shows the influence of the environment partially on the level of job satisfaction experienced by employees. The findings indicate a significant effect of both compensation and the physical work environment on employee job satisfaction, as evidenced by the results of the F test. The analysis of the coefficient of determination shows that the value of the adjusted R square is 0.821. This means that the compensation and physical work environment variables can explain 82.1 per cent of the employee job satisfaction variable variance. In comparison, the remaining 17.9 per cent of the variance is due to other variables.